Religious Moderation in Indonesian Context - Hakim, Lukmanul; Meria, Aziza; Suryadinata, Sartika (Al-Albab, 2023)
This paper aims to explore the concept of religious moderation across Islamic history within Indonesian context. The method used is qualitative with a historical approach. The historical approach is used to reformulate the concept of religious moderation in modern times and classical times. The results showed that religious moderation in modern times correlates with religious moderation in classical times. Although the term religious moderation was only promoted by the Ministry of Religious Affairs of Indonesia in 2019, in terms of practice it has been carried out by the Prophet who was then continued by the companions and the people after him. Classical and modern religious moderation both focus on establishing harmonious and peaceful social relations with people of different religions. However, there are some differences between modern and classical moderation, namely: First, in modern times religious moderation is focused on improving and maintaining relations between Muslims and people of other religions by providing several indicators related to this. Whereas in the classical period, this religious moderation focused on their freedom to embrace their religion without any coercion to convert to Islam. Second, in modern times the term moderation is used in the hope of being an antidote to the many conflicts, while in classical times religious moderation was practiced by the Prophet to serve as an example for the companions and subsequent people. Third, the practice of religious moderation in terms of tolerance towards people of other religions in modern times looks very tolerant by congratulating each other on the holidays of other religions, while in classical times religious moderation only centred on giving them the freedom to choose their religion and carry out their religious worship.